Prevalence and Treatment of Maxillary Incisivo-Canine Block Anomalies at the Donka National Hospital in Conakry (Global Journal of Medical Research, 2023)
Introduction Orthodontic anomalies are deviations from normality variations in the morphology and functions of the orofacial sphere Many types of dental anomalies can be observed in the anterior region and can cause real aesthetic damage to our patients The objectives of this study were to determine the prevalence of orthodontic anomalies of the maxillary incisivo-canine block to identify the orthodontic anomalies of the maxillary incisivocanine block encountered and to describe the type of appliance used to manage these anomalies Material and methods This was a prospective descriptive study lasting one year from 1erAout 2020 to 1erAout 2021 Our data were collected using a survey form The study included all elderly patients from 9 to 26 years of age in whom one or more orthodontic anomalies of the maxillary incisivocanine block were detected and managed during the study period
Keywords: abnormalities; incisivocanine block; maxilla; treatment